Soluble factors from stellate cells induce pancreatic cancer cell proliferation via Nrf2-activated metabolic reprogramming and ROS detoxification - Wu, Y; Looi, C; Subramaniam, K; Masamune, A; Chung, I (Impact Journals, 2016)
Pancreatic stellate cells (PSC), a prominent stromal cell, contribute to the progression of pancreatic ductal adenocarcinoma (PDAC). We aim to investigate the mechanisms by which PSC promote cell proliferation in PDAC cell lines, BxPC-3 and AsPC-1. PSC-conditioned media (PSC-CM) induced proliferation of these cells in a dose- and time-dependent manner. Nrf2 protein was upregulated and subsequently, its transcriptional activity was increased with greater DNA binding activity and transcription of target genes. Downregulation of Nrf2 led to suppression of PSC-CM activity in BxPC-3, but not in AsPC-1 cells. However, overexpression of Nrf2 alone resulted in increased cell proliferation in both cell lines, and treatment with PSC-CM further enhanced this effect. Activation of Nrf2 pathway resulted in upregulation of metabolic genes involved in pentose phosphate pathway, glutaminolysis and glutathione biosynthesis. Downregulation and inhibition of glucose-6-phosphate-dehydrogenase with siRNA and chemical approaches reduced PSC-mediated cell proliferation. Among the cytokines present in PSC-CM, stromal-derived factor-1 alpha (SDF-1α) and interleukin-6 (IL-6) activated Nrf2 pathway to induce cell proliferation in both cells, as shown with neutralization antibodies, recombinant proteins and signaling inhibitors. Taken together, SDF-1α and IL-6 secreted from PSC induced PDAC cell proliferation via Nrf2-activated metabolic reprogramming and ROS detoxification.